Технологічні основи зміцнення листового скла контактним гартуванням - Серкіз, Оксана Костянтинівна (Національний університет "Львівська політехніка", 2015)
Дисертація присвячена розробленню технології контактного гартування скла для забезпечення його високої міцності і надійності в процесі експлуатації при мінімізації витрат на електроенергію. Сучасні технології зміцнення скла методом термічного гартування характеризуються значною енергоємністю, оскільки для ефективного охолодження необхідно використовувати високопотужні вентилятори. У даній роботі пропонується новий спосіб гартування скла, в якому заміна охолоджувального агенту із повітряного на водяний дасть змогу у значній мірі знизити енерговитрати. На основі аналізу процесів формування залишкових напружень у склі розроблено оптимальні режими охолодження системи «теплопровідні пластини - скло» та описано вплив параметрів гартування на вигляд епюри розподілу напружень у склі. Встановлено взаємозв’язок між фізико-хімічних властивостями гартованого скла та структурними особливостями поверхневого шару. На основі результатів пошарового дослідження зони стиску вказано основні причини зменшення мікротвердості та хімічної стійкості гартованого скла. Розроблено напівпромислову установку гартування скла контактним методом. Завдяки контролю температури поверхні та центральних шарів скла показано особливості процесу охолодження через шар теплопровідного матеріалу порівняно із традиційним. Встановлено, що ступеневе нагрівання до температури гартування дає можливість підвищити величину залишкових напружень стиску на поверхні скла. У роботі також наведено економічну ефективність запропонованої технології гартування скла контактним методом. Диссертация посвящена разработке технологии контактной закалки стекла для обеспечения его высокой прочности и надежности в процессе эксплуатации при минимизации затрат на электроэнергию. Современные технологии упрочения стекла методом термического закаливания характеризуются значительной энергоемкостью, поскольку для эффективного охлаждения необходимо использовать высокомощные вентиляторы. В данной работе предлагается новый способ закалки стекла, в котором замена охлаждающего агента с воздушного на водяной позволит в значительной степени снизить энергозатраты. На основе анализа процессов формирования остаточных напряжений в стекле разработаны оптимальные режимы охлаждения системы «теплопроводные пластины - стекло» и описано влияние параметров закаливания на вид эпюры распределения напряжений в стекле. Установлена взаимосвязь между физико-химических свойствами закаленного стекла и структурными особенностями поверхностного слоя. На основе результатов послойного исследования зоны сжатия указаны основные причины уменьшения микротвердости и химической устойчивости закаленного стекла. Разработана полупромышленная установка закалки стекла контактным методом. Благодаря контролю температуры поверхности и центральных слоев стекла показаны особенности процесса охлаждения через слой теплопроводного материала по сравнению с традиционным. Установлено, что ступенчатый нагрев до температуры закалки позволяет повысить величину остаточных напряжений сжатия на поверхности стекла. В работе также приведена экономическая эффективность предлагаемой технологии закалки стекла контактным методом. The thesis is dedicated to the development of technology of glass contact tempering for providing its high durability and reliability during operation with minimized energy costs. Modern technologies of glass strengthening by thermal tempering are characterized by significant energy consumption, because for the efficient cooling it is necessary to use high-power vans. It is proposed a new way of glass tempering in which the replacement of air cooling agent to water one reduces the energy consumption. The optimum cooling regimes of the system "heat conducting plates - glass" are developed based on the analysis of the formation of residual stresses. During tempering between the plates based on Si the consumption of water is 0.45 l /(s∙m2), cooling time is 45 s; for plates based on Si-Al: consumption of water is 0.60 l/(s∙m2), cooling time is 35 s. This method of cooling leads to an increase in the thickness of compressed layer and the parameter χ (ratio of compressive stresses to tensile ones). For air tempering at compression stress value of 110 MPa χ is 2.1, while for contact one this parameter can reach 2.9. Moreover, in the traditional method of tempering the tensile stress value in the middle layer exceeds the ultimate tensile strength and glass is not subject to machining. In the glass, tempered by contact method, tensile stresses are within 38-44 MPa, which makes it possible to carry out drilling and cutting glass after tempering. The interrelation between the physical and chemical properties of tempered glass and structural features of the surface layer is established. The determination of microhardness as the tempered glass surface characteristics should be organised in certain conditions that make it possible to get the most reproducible results. It is necessary to limit the plasticizing effect of water on the glass surface by drying and provide optimum conditions for micro-plastic penetration regime of the indenter (indenter load is 100 g, the time of holding is 15 s). On the basis of layer density research the presence of tempered glass layer thickness of 0.01 mm with lower density was found. For samples tempered by air its density is 67 kg /m3, for samples tempered by contact method - 42 kg/m3. This phenomenon explains features of microhardness changes in tempered glass. The surface energy of tempered samples is greater than initial ones, indicating a lower conection degree of siloxane bonds. This shift is confirmed by IR spectra peak stretching of Si - O - Si vibration from 1065 to 1050 cm-1. The heat resistance of glass after tempering increases by 75% (from 70 to 125 0C) and hydrophobicity increases by 20% (from 35 to 420). Chemical resistance decreases as a result of tempering an average of 25%, but samples tempered by contact method is more resistant against acid than samples tempered traditionally. Contact tempering makes it possible to increase the strength of glass from 60 to 182 MPa, which is 15% greater than tempered traditionally. Semi industrial machine of glass tempering by contact method was developed. Due to the temperature control of surface and central layers of glass it is shown the features of cooling process through a layer of heat-conductive material compared to traditional one. It is shown the change in temperature during glass tempering by contact method comparing with traditional one. At the time of reaching of the inner layer surface Tg, the temperature of glass, tempered by contact method is 50 0C lower, contributing to the formation of more intense contraction. The combination of surface layer etching of tempered glass and protective coating application allows to eliminate the defective layer and increase the strength of glass from 60 to 187 MPa in the case of air tempering and to 210 MPa in the case of contact one. It is established that the step heating of glass to the tempering temperature makes it possible to increase the value of residual compressive stresses on the surface. Due to the change in value of glass thermal coefficient of linear expansion during isothermal holding the value of residual stress increases from 2.6 to 2.8 order/cm.The paper also shows the cost-effectiveness of the proposed technology of contact tempering.
Технологические основы упрочения листового стекла контактным закаливанием
Fundamentals of glass strengthening by contact method
Keywords: гартування; флоат-скло; напруження; мікротвердість; густина; закалка; флоат-стекло; напряжение; микротвердость; плотность; tempering; float glass; residual stresses; microhardness; density